Do livro ilustrado ao aplicativo: reflexões sobre multimodalidade na literatura para crianças - Giselly Lima de Moraes (Estudos de Literatura Brasileira Contemporânea)
This paper reflects on the diversity of semiotic resources in contemporary children’s literature, analyzing the impact of technology on the literary text. Using some concepts from the studies of multimodality, we examine the potential of sense resulting fr om the relationship between verbal and nonverbal features in print and digital literature, in works such as Flicts ; “A girafa” and “Cigarra”, from Angela Lago’s series “Ave, palavra”; and the application of literature for children Es así , by Paloma Valdivi a. The author presents evidence to assert that the advances in multimodality studies help improving the literary experience by children nowadays, as it offers ways to know and mediate the process of interpretation and enjoyment of multimodal texts.